Gender agreement in Qurʾānic VSO verbs with nonhuman subjects - Hanitsch, Melanie (Zeitschrift für Arabische Linguistik, 2022)
Variation in gender agreement of Arabic VSO verbs is a highly complex but underinvestigated syntactic phenomenon. This contribution focuses on the agreement variation found specifically with Qurʾānic nonhuman plural subjects. In fact, while the rate of “strict” gender agreement in the f.sg. is rather high (84%), there also is a remarkable rate of agreement in the m.sg. (16%)—or, in other terms, of omission or neutralization of agreement. The phenomenon is contextualized within the spectrum of diachronic as well as diatopic varieties of Arabic and then submitted to a fine-grained analysis. Four variables are examined as to their effect on the agreement outcome: 1) distance between verb and subject, 2) plural formation, 3) lexical gender, and 4) animacy degree of the subject (referents). It is shown that distance is the most influential variable, insofar as it stakes out the frame for the effect of the other variables. The effects of plural formation and animacy are closely intertwined, and—quite surprisingly—lexical gender has a weak, however measurable, effect. There also is ample evidence for priming and agreement attraction (sometimes caused by “pseudo controllers”).
CRIS-Team Scopus Importer:2024-12-16
Keywords: agreement; animacy; gender; language variation; Qurʾānic Arabic; VSO; word order